Primary Amebic Meningoencephalitis Associated With Rafting on an Artificial Whitewater River: Case Report and Environmental Investigation. (19th September 2017) - Cope, Jennifer R; Murphy, Jennifer; Kahler, Amy; Gorbett, Daniel G; Ali, Ibne; Taylor, Brandi; Corbitt, Lisa; Roy, Shantanu; Lee, Nicole; Roellig, Dawn; Brewer, Scott; Hill, Vincent R
Abstract : Naegleria fowleri is a thermophilic ameba found in freshwater that causes primary amebic meningoencephalitis (PAM). This article describes a PAM case in an 18-year-old woman who was exposed to N. fowleri while rafting on an artificial whitewater river. Abstract: Background: Naegleria fowleri is a thermophilic ameba found in freshwater that causes primary amebic meningoencephalitis (PAM) when it enters the nose and migrates to the brain. Patient exposure to water containing the ameba typically occurs in warm freshwater lakes and ponds during recreational water activities. In June 2016, an 18-year-old woman died of PAM after traveling to North Carolina, where she participated in rafting on an artificial whitewater river. Methods: We conducted an epidemiologic and environmental investigation to determine the water exposure that led to the death of this patient. Results: The case patient's most probable water exposure occurred while rafting on an artificial whitewater river during which she was thrown out of the raft and submerged underwater. The approximately 11.5 million gallons of water in the whitewater facility were partially filtered, subjected to ultraviolet light treatment, and occasionally chlorinated. Heavy algal growth was noted. Eleven water-related samples were collected from the facility; all were positive for N. fowleri . Of 5 samples collected from the nearby natural river, 1 sediment sample was positive for N. fowleri . Conclusions: This investigation documents a novel exposure to an artificial whitewater river as the likely exposure causing PAM in this case. Conditions in the whitewater facility (warm, turbid water with little chlorine and heavy algal growth) rendered the water treatment ineffective and provided an ideal environment for N. fowleri to thrive. The combination of natural and engineered elements at the whitewater facility created a challenging environment to control the growth of N. fowleri .